サハリン発見「アイヌ鎧」の年代について - 梶原, 洋; カジワラ, ヒロシ; Kajiwara, Hiroshi (東北福祉大学芹沢銈介美術工芸館, 2021)
1933 年に伊東信雄により樺太で発見された2 領のアイヌ鎧は、主としてその構造が古墳時代の挂甲に類似していることから、平安初期（9 世紀）の所産と推定されていた。しかし、11 から12 世紀に生まれ、鎌倉時代以降に盛んに用いられた「腹巻鎧」との構造的な類似性をもつと推定される。そして、鎧自体の特徴は、北東アジアのチュクチ族などの前合わせ式鎧と共通していて、その伝統に倣った上で、日本式鎧の縄目縅、菱縫などの製作技法を取り入れて作られた可能性が高い。また、サハリンに残されたアイヌ鎧に見られる巴文が、南北朝以降の型式であり、新たに確認された松皮菱文は、武田氏に関連することから、15世紀に蠣崎氏（武田氏）を中心とした道南の和人勢力とアイヌ民族との間で繰り広げられた戦いとの強い関連も推定される。したがって、この鎧は、平安時代9 世紀の所産ではなく、室町時代の15 世紀頃に奥州以北などで製作され、サハリン（樺太）にまでもたらされたとの説明が最も有力となり、従来の年代感は訂正されなくてはならないだろう。 Two unique works of lamellar armors made of hide have been preserved ndividually at Tohoku University in Sendai and at a regional museum in Yuzhno-Sakhalinsk, Russia (fig.1,6). They were originally found by and purchased from a Karafuto Ainu family by the late Professor Itoh Nobuo in 1933. One of them was transported to Sendai and another one remains in Sakhalin. Suenaga Masao and Itoh pointed out that the armor shares common structural characteristics between the Karafuto armors and the Keiko armor (front fastening iron lamellar armor). That was originally excavated inside the Kofun (Tumuli) as grave goods after the 5th century. Based mainly on this feature, both scholars dated the Ainu armor back to the early Heian period, i.e. the 9th century as a remnant example of Keiko tradition. However, I have recently noticed a critical resemblance in structure between Japanese Haramaki armor (in reversed wearing), that appeared around 12th century, and Ainu armors (fig.7). As Suenaga and Itoh had already referred, front alignment structure was common among armors of Eurasian ethnic groups including the Ainu (fig.2, 3) (Suenaga and Itoh 1979). Aa a result, the Ainu armors display both traditions, front aligning structure derived from Eurasia and lacing techniques for Lamellae as Nawameodoshi (oblique lacing) or Hishinui (cross lacing) (fig.4). The front and dorsal plates are equivalent to those of the Haramaki cuirass in reversed position of Japanese origin (fig.7). Additionally, the counterclockwise Tomoe crest on Sakhalin armor resembles the style of Nanbokucho period or ...